A global analytical molecular pharmacological study of the endocrinological pharmacotherapeutic rationale of anti-diabetic prescriptions appraisal attributes for metformin and sitagliptin, with evaluation of anti-diabetic tertiary medical healthcare patient satisfaction - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The inhibition of dipeptidyl peptidase-4 by anti-diabetic drugs dipeptidyl peptidase-4 inhibitors enhances hormonal activity of incretins (GLP-1, GIP, GRP), stimulates insulin release and reduces glucagon secretion, producing anti-hyperglycaemic activity among type II diabetics. The objective of this study was a global analytical molecular pharmacological study of the endocrinological rationale of anti-diabetic prescriptions appraisal attributes for metformin and sitagliptin, along with anti-diabetic tertiary medical healthcare patient satisfaction evaluation. Methods: 100 new early moderate grade type II diabetics were prescribed oral metformin 500 mg or sitagliptin 25 mg once daily for 3 months, in monotherapy, or in combination therapy, or in a mixed regimen of monotherapy and combination therapy. The patients’ endocrinological pharmacotherapeutic compliance was analysed. The number of prescriptions for metformin and sitagliptin was recorded; and prescription percentages were calculated. The completeness and molecular basis of prescription content attributes were analysed. The molecular basis of anti-diabetic pharmacotherapeutics, was analysed. The anti-diabetic tertiary medical healthcare patient satisfaction was evaluated by patient response to different attributes of anti-diabetic treatment. Results: All the patients had completed the study, with no adverse effects related drop-out, lost to follow-up or voluntarily withdrawn patients. The prescription rates of metformin was 75% (75 prescriptions), followed by sitagliptin: 25% (25 prescriptions).100% prescriptions were complete for each prescription content attribute. The molecular pharmacotherapeutic response mechanisms were significantly efficacious. All the patients were satisfied with each anti-diabetic medical healthcare attribute. Conclusions: The patient endocrinological pharmacotherapeutic compliance was significantly high. Metformin was most commonly prescribed, followed by sitagliptin. The prescription content analyses showed 100% completeness, with significant pharmacotherapeutic molecular efficacy. There was ample anti-diabetic medical healthcare satisfaction.